Hosanna in the Highest - Hart, Henry St. John (Scottish journal of theology, 1992)
This paper was originally delivered on 6th May 1977 as the Presidential Address of the Cambridge Theological Society. It has been lightly edited and prepared for publication with the author's help by Dr William Horbury and Professor J. C. O'Neill, in honour of the author and in gratitude for his teaching and inspiration on his 80th birthday, 15th April 1992.